PENDIDIKAN POLITIK OLEH PARTAI POLITIK DI JAWA TENGAH (Studi Komparasi Partai Demokrasi Indonesia Perjuangan dan Partai Keadilan Sejahtera) - Haniatul Mufidah; Nur Hidayat Sardini (Journal of Politic and Government Studies, 2026)
Political education is one of the strategic functions of political parties mandated by Law Number 2 of 2011, encompassing education for party cadres and members (internal) as well as for the general public (external). In practice, however, its implementation remains varied and has yet to be fully effective. This study aims to analyze the forms of political education programs conducted by Indonesian Democratic Party of Struggle (PDI Perjuangan) and the Prosperous Justice Party (PKS) in Central Java and to evaluate their implementation, by comparing two parties with distinct ideological foundations while simultaneously analyzing both dimensions of political education, namely the internal and external dimensions. This study employs a qualitative comparative-descriptive method, with data collected through in-depth interviews, observation, and documentation, and analyzed using the Miles and Huberman model. The findings indicate that ideological orientation is the determining factor shaping each party's approach to political education. In the internal dimension, PDI Perjuangan implements a three tier cadre system centered on Pancasila, Marhaenism, and the teachings of Bung Karno. PKS conducts weekly cadre development through the Member Development Unit (UPA) using a standardized curriculum that integrates Islamic values and leadership principles. In the external dimension, PDI Perjuangan reaches the public through community-based social activities, while PKS engages society through social services, public seminars, and political outreach. PDI Perjuangan excels in the breadth and inclusivity of its public outreach, while PKS excels in the depth of cadre development. Evaluation reveals that neither party has fully met the three indicators stipulated under Law Number 2 of 2011, namely increasing public awareness of civic rights and obligations, enhancing political participation, and fostering national character and civic independence. Key obstacles include political pragmatism among the public, the prevalence of money politics, and disparities in the distribution of state political funding across regions. This study concludes that party ideology concretely shapes the direction and methods of political education. However, existing regulations have yet to be capable of guaranteeing substantive and equitable political education quality, particularly for the general public as the primary external target.